The Influence of Pattern-Bargaining on Manufacturing Wages in the Cleveland, Ohio, Labor Market, 1945-1950 - Locks, Mitchell O. (The Review of Economics and Statistics, 1955)
Mitchell O. Locks, The Influence of Pattern-Bargaining on Manufacturing Wages in the Cleveland, Ohio, Labor Market, 1945-1950, The Review of Economics and Statistics, Vol. 37, No. 1 (Feb., 1955), pp. 70-76